Segmental congenital smooth muscle hamartoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Congenital leiomyoma is a hamartoma of smooth muscle cells. The latter are found in the erector muscles of the hair and in the wall of arteries and veins of the skin. This last localization could explain the aspect of vascular lesion, exceptionally reported in the literature (1, 2). Congenital leiomyoma occurs clinically in the first days of life as a plaque or multiple follicular papules covered by normal skin and therefore poorly visible; it is often associated with hypertrichosis. Characteristic is the palpatory finding characterized by temporary induration, rippling and sometimes fasciculation of the lesions due to the coordinated contraction of smooth muscle cells. This sign, also known as pseudo-Darier, differs from the Darier’s sign due to the lack of erythema, of wheal and for its shorter duration. Congenital leiomyoma is a benign lesion that tends to become less evident over time and usually does not require any therapy.